Akibat Hukum Perjanjian Nominee Hak Atas Tanah Berkaitan Dengan Kepemilikan Warga Negara Asing - Khairunnisa Khairunnisa; Mohamad Fajri Mekka Putra (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2022)
The purpose of this research is to analyse the legal effect towards foreigner on the proprietary rights over land in Indonesia using nominee agreement. The research method that is used in this research is normative-juridical method with document analysis approach through library research sourced from legislations, books, legal articles, and court’s ruling. As for the analysis method used this research is qualitative which compare written regulation with the reality that happened related to the use of nominee agreement towards proprietary rights over land by foreigner in Indonesia. The result shows that the use of nominee agreement for proprietary rights over land by foreigner is null and void. The legality of the agreement is dubious because it does not satisfy the requirement for the validity of agreements, that is a legal cause. There is no legal protection towards notary who issued nominee agreement.